Conceptions of health and action of the Black Movement in Brazil in a health policy - Araújo, Marcos Vinícius Ribeiro de; Teixeira, Carmen Fontes de Souza (Saúde e Sociedade, 2023)
The institutional frameworks that culminated in the National Health Policy for the Black Population (PNSIPN), documented in the literature, cite the Black Movement (MN) as a key political actor. However, the participation of this collective actor, heterogeneous and diverse, leads us to inquire about their conceptions, claims and political action in health care, problematizing both their closeness and distance from the Health Reform Movement (MRSB). Thus, this study analyzes the conceptions and political action of the MN organizations in the process of elaborating the PNSIPN. Semi-structured interviews were conducted with leaders, and the content of documents published on the organizations’ official websites were analyzed. Results show that the leaders developed conceptions about the health-disease process based on the notion of structural racism, which guided the development of the political agenda, the definition and articulation of strategic alliances and forms of action in the public sphere. None of these processes mentioned articulations with MRSB entities, although the MN’s political practices in combating racism in health care suggest closer relations between the Black Movement and the MRSB.